Seismic signal processing for single well imaging applications - Walsh, Brendan (The University of Edinburgh, 2007)
This thesis focuses on the concept of Single Well Imaging (SWI) in which a seismic source and receivers are deployed in a borehole to investigate the surrounding geology. The Uniwell project (1997-1999) was the first attempt to develop the SWI method; it used a fluid-coupled downhole source, which unfortunately generated high amplitude guided waves in the borehole which obscured all other useful information. Initial research work detailed in this thesis focused on removing the high amplitude guided waves, known as tube waves. Two-step source signature deconvolution using first the recorded source signature, and then the tube-wave reflected from the bottom of the well, succeeded in compressing the tube wave. The results were not consistent across all receivers, but there is enough correlation to identify a P-wave. Further work concentrates on using a new technique called Empirical Mode Decomposition to separate the tube-wave mode from the data. This identifies three dominant modes and a possible body wave arrival, but the results are ambiguous due to the inability of the decomposition to focus on the narrow bandwidth of interest. The source signature deconvolution technique can also be used to process real-time vertical seismic profiling (VSP) data down-hole, during pauses in drilling, in what is referred to as a Seismic-While-Drilling (SWD) setup. Results show that the technique is versatile and robust, giving 1 ms precision on first-break picking even in very noisy data. I also apply the technique to normal VSP data to improve both the resolution and the signal-to-noise ratio. A major effort in this thesis is to consider the effect of a clamped downhole source to overcome the tube-wave problem, using a magnetostrictive source. Earlier work established that the use of a reaction mass tended to excite resonances in the tool which caused the transducer to break. A new design for the source was developed in cooperation with colleagues which utilises a hydraulic amplifier design and a low power coded waveform driving method exploiting the time-bandwidth product to extract the signal from the noise. My results show that as the run time increases the resolution improves. With a run length of 80s it is possible to resolve the signal transmitted 50 cm through a granite formation. This analysis led to a revised design of the source to improve its efficiency. I have used finite difference modelling, with a variable grid technique, to compare an ideal explosive source with an ideal clamped source. The fluid-coupled source emits high amplitude tube waves which virtually obscure the body wave, whereas the clamped source emits a clearly identifiable P-wave along with lower amplitude tube waves. This clearly illustrates the advantage of an ideal clamped source. To model the source more accurately the idealwavelet is replaced by the respective recorded source signatures, and the data is then processed by cross correlation with the appropriate signature. The results show that the coded waveform approaches the resolution of the ideal wavelet very well, with all major events being visible. However, the fluid-coupled source performs very poorly with only the highest amplitude tube-wave visible. This work illustrates that by replacing a fluid-coupled source by a clamped source driven by a coded waveform, and by processing the data using cross correlation or signature deconvolution, it is possible to minimise or eliminate tube-wave noise from a SWI survey. It is hoped that the results outlined here will provide the basis for a new SWI method than can be used to prolong the supply of North Sea oil.
Keywords: Single Well Imaging (SWI); Geophysics; Seismic Imaging